The Development of Community-Based Tourism in “Kampung Inggris” Pare, Kediri Regency, East Java - Lely Indah Mindarti; Ronny Subroto Suryo Guritno (Institut Agama Islam Negeri Madura, 2019)
From year to year, many students, college students or other people in general come to Kampung Inggris. It is a strategic opportunity in tourism sector, especially in educational tourism. Therefore, it requires the cooperation of the three pilars for the development and management of good tourism. Good tourism governance basically is coordination and synchronization among the three pillars (government, private sectors, and society). Based on the objectives of the research, this study used a descriptive method with qualitative approach. This study indicates that the three pillars of tourism management service in “Kampung Inggris” were still not good. It can be proven by the lack of government function (seemed apathetic) to the development of “Kampung Inggris”. From the function of the three pillars, the influence of the society was very dominating. Thus, “Kampung Inggris” was considered as a Community-Based Tourism (CBT). CBT is one of the conventional tourism developments by developing the economic potential of the society. It should also try to enhance the value, dignity, confidence, and protect the system of cultural values and religious values in society.